Thermal Treatment of Construction Waste: A Waste Management Approach in Malaysia (International Journal of Built Environment and Sustainability, 2025)
Thermal treatment of waste materials is identified as one of the potential methods in waste management practice. The method is currently implemented in Malaysia for municipal solid waste and it is believed that thermal treatment processes are suitable too for certain types of construction waste materials. Therefore, this study aimed to identify the chemical properties of construction waste materials in terms of moisture content, volatile matter, ash content and fixed carbon through proximate analysis to determine the possible construction waste materials that can be included in thermal treatment processes. The findings of the proximate analysis showed that wood waste recorded 85.11% volatile matter with 1.28% ash content, while plastic waste recorded 90.19% volatile matter with 7.50% ash content. It was understood that the higher the percentage of volatile matter in a particular material, the longer the combustion process, hence, the higher the heating value might be generated. For that reason, wood and plastic waste from the construction industry could be a great source for thermal treatment processes and heat energy generation since both materials are highly volatile matter with relatively low ash content or residuals. The minimal residuals could preserve our landfill space and lessen the environmental impacts.
Keywords: Thermal treatment, Construction waste, Sustainability, Proximate analysis